Hubungan Antara Karakteristik dan Persepsi Petani Padi Organik dengan Adaptasi Perubahan Iklim di Kecamatan Pagerageung - Larasati , Resti; Nuraini, Candra; Heryadi, D. Yadi (Lembaga Pengembangan Kinerja Dosen, 2025)
Climate change has a significant impact on organic rice cultivation, which depends heavily on environmental conditions. This study aims to: (1) identify the characteristics of organic rice farmers in Pagerageung District, (2) examine farmers’ perceptions of climate change, (3) analyze farmers’ adaptation strategies to climate change, and (4) assess the relationship between farmers’ characteristics and perceptions with their adaptive capacity. The research employed a quantitative survey method using a census technique involving 44 farmers, with data collected through questionnaires, interviews, and observations. The results showed that: (1) farmers’ characteristics were at a moderate level (score 534/880), (2) farmers’ perceptions were high (score 1,686/2,112), (3) adaptation was moderate (score 1,548/2,112) with economic adaptation being the highest, and (4) there was a significant relationship between farmers’ characteristics (ρ = 0.504; p = 0.000) and perceptions (ρ = 0.431; p = 0.000) with their adaptation to climate change. Simultaneously, Kendall’s W test (0.506; p = 0.000) indicated a significant relationship between farmers’ characteristics and perceptions with their adaptive capacity to climate change.